DEVELOPMENT OF EFFECTIVE ALGORITHMS OF SURFACE WATER POLLUTION DIAGNOSTICATION - Zatserkovnyy, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper presents the following algorithm for the diagnosis of pollution of water objects: the theoretical bases for diagnosing the characteristics of the deterioration of the water objects condition (occurrence of malfunctions) with the deviation of their parameters from the standard ones on the steady or close to the steady (quasi-steady) modes of pollution development and further assessment of the level of risk of occurrence of a dangerous situation, the approval of management decisions on liquidation or minimization of this pollution impact on the ecology of the water object. The development of effective algorithms of pollution identification at the initial stages of pollution of water resources will enable an assessment of the nature and level of water pollution with the increasing number of chemicals associated with an increase of anthropogenic pressure on water objects. To simulate the processes occurring in the aquatic environment, it is proposed to use the geographic information system (GIS). The conducted studies indicate that the borders of identification of the initial development of the process of pollution spreading (the occurrence of malfunction) is largely determined by the number of parameters that are measured in the process of diagnosis. The sensitivity of this diagnostic method for the majority of one-dimensional malfunctions is proved.